2015
DOI: 10.1002/elsc.201400230
|View full text |Cite
|
Sign up to set email alerts
|

Changing growth behavior of heavy‐metal tolerant bacteria: Media optimization using droplet‐based microfluidics

Abstract: Overproduction of secondary metabolites requires know-how for media optimization and design of effective screening procedures. Micro-segmented flow was applied to test the growth characteristics of heavy-metal tolerant soil bacteria (Bacillus sporothermodurans and Streptomyces tendae) toward changing media composition. The applied microfluidic technique was shown to be suitable for media optimization, with effects of media solutes like phosphorus and nitrogen, and a trace metal solution. For inorganic phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…113 In a series of projects, the group of M. Köhler used automated droplet systems 109 for studies on i) the toxicity of an industrial pollutant 2,4-dinitrophenol (DEP) as a single agent 130 and in combination with silver and gold nanoparticles; 131 ii) the antimicrobial function of a candidate peptide, 130 also in combinations with nanoparticles; 132 iii) the impact of caffeine and a hypertension drug to antibiotic coadministration 133 and iv) the combinatorial effect of metal ions and media composition on heavy metal-tolerant bacteria. 110,134,135 Other similar examples of studies that used droplet microfluidic platforms to generate antibiotic gradients to assess the antimicrobial susceptibility of bacteria can be found in ref. 115, 117 and 136. Cho et al demonstrated a droplet-based platform for highthroughput screening of photosensitizer activity, that is, a chemical compound that undergoes a controlled light-induced change from a non-toxic to a toxic state for bacterial cells.…”
Section: Applications Of Droplet Microfluidics In Microbiologymentioning
confidence: 99%
“…113 In a series of projects, the group of M. Köhler used automated droplet systems 109 for studies on i) the toxicity of an industrial pollutant 2,4-dinitrophenol (DEP) as a single agent 130 and in combination with silver and gold nanoparticles; 131 ii) the antimicrobial function of a candidate peptide, 130 also in combinations with nanoparticles; 132 iii) the impact of caffeine and a hypertension drug to antibiotic coadministration 133 and iv) the combinatorial effect of metal ions and media composition on heavy metal-tolerant bacteria. 110,134,135 Other similar examples of studies that used droplet microfluidic platforms to generate antibiotic gradients to assess the antimicrobial susceptibility of bacteria can be found in ref. 115, 117 and 136. Cho et al demonstrated a droplet-based platform for highthroughput screening of photosensitizer activity, that is, a chemical compound that undergoes a controlled light-induced change from a non-toxic to a toxic state for bacterial cells.…”
Section: Applications Of Droplet Microfluidics In Microbiologymentioning
confidence: 99%
“…Therefore, different batches of the investigated microorganism are treated with increasing amount of the effector and the temporal development of the cell number is monitored. If microorganisms are investigated with different doses of effectors (C=0 < C=1 < C=2 < C=3) the proliferation can be influenced in three different ways: (1) The lag phase is prolonged, but the organism proliferates thereafter without restrictions (Figure 1A); (2) The organism proliferates but in dependence on the effector concentration with different growth rates in the exponential phase (Figure 1B); (3) The organism proliferates but the maximum cell density in the stationary phase depends on the effector. A similar behavior will be observed if the cell morphology is changed by the effector.…”
Section: Dose-response Screening Backgroundmentioning
confidence: 99%
“…Microbiological culture screening plays an important role in different application fields. Microbiological cell assays are intensively used in context of medical [1], environmental [2,3], food [4], bioprocess or pharmaceutical [5] screening tasks. Important applications are e.g., the antibiotic susceptibility testing [6][7][8][9] of patient samples or profiling of new chemical compounds for antibiotic drug development [10][11][12].…”
Section: Introductionmentioning
confidence: 99%